2003
DOI: 10.1103/physreve.68.011102
|View full text |Cite
|
Sign up to set email alerts
|

Average size of random polygons with fixed knot topology

Abstract: We have evaluated by numerical simulation the average size R(K) of random polygons of fixed knot topology K=,3(1),3(1) musical sharp 4(1), and we have confirmed the scaling law R(2)(K) approximately N(2nu(K)) for the number N of polygonal nodes in a wide range; N=100-2200. The best fit gives 2nu(K) approximately 1.11-1.16 with good fitting curves in the whole range of N. The estimate of 2nu(K) is consistent with the exponent of self-avoiding polygons. In a limited range of N (N greater, similar 600), however, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 25 publications
4
71
0
Order By: Relevance
“…He argued that the radius of gyration would then scale as n with Ϸ 0.588, the value appropriate for self-avoiding polygons or for rings with excluded volume. While this topological expansion might seem surprising at first sight there is growing evidence that the prediction is correct Matsuda et al, 2003;Moore et al, 2004͒. The asymptotic behavior of the average size of ring polymers with fixed topology has also been studied for an off-lattice model in which self-avoiding polygons consist of N cylinders with radius r. By varying r Deguchi ͑2001, 2002͒ showed that the topological expansion strongly depends on the radius r. For small r ͑where the model is closer to the Gaussian random poly-gon͒ the effect is indeed significant, but it becomes less important as the radius r increases, i.e., as the selfavoidance becomes more and more relevant.…”
Section: B Metric Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…He argued that the radius of gyration would then scale as n with Ϸ 0.588, the value appropriate for self-avoiding polygons or for rings with excluded volume. While this topological expansion might seem surprising at first sight there is growing evidence that the prediction is correct Matsuda et al, 2003;Moore et al, 2004͒. The asymptotic behavior of the average size of ring polymers with fixed topology has also been studied for an off-lattice model in which self-avoiding polygons consist of N cylinders with radius r. By varying r Deguchi ͑2001, 2002͒ showed that the topological expansion strongly depends on the radius r. For small r ͑where the model is closer to the Gaussian random poly-gon͒ the effect is indeed significant, but it becomes less important as the radius r increases, i.e., as the selfavoidance becomes more and more relevant.…”
Section: B Metric Propertiesmentioning
confidence: 96%
“…This implies that ͑͒ = ͑͒ and A ͑͒ = A ͑͒ for all . There is general agreement that ͑͒ is independent of ͑Janse van Rensburg and Whittington, 1991a;Quake, 1994Quake, , 1995Matsuda et al, 2003͒. Although there has been some disagreement about the constancy of the amplitude, there is a growing amount of numerical evidence that it is constant.…”
Section: B Metric Propertiesmentioning
confidence: 99%
“…In all the works (7)(8)(9), to extract the value of scaling exponent from the data, which (particularly in ref. 7) is almost entirely restricted to the crossover range, authors fitted the data using the formula:…”
Section: [2]mentioning
confidence: 99%
“…These works belong to the direction [26,27,28,29,30] addressing the spatial statistics of polymer loops restricted to remain in a certain topological knot state. It turns out that even for loops with no excluded volume and thus are not self-avoiding, N 0 marks the crossover scale between mostly Gaussian (N < N 0 ) and significantly non-Gaussian (N > N 0 ) statistics.…”
Section: Introduction: Formulation Of the Problemmentioning
confidence: 99%